ANALISIS PROGRAM STRATEGIS DALAM PENGELOLAAN LAHAN KRITIS DAS BILA (Analysis of Strategic Program of Critical Land Bila Watershed Management) - Andi Nuddin (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2011)
The rehabilitation program of critical land had been done since 1985 until 2001, but Bila watershedcondition did not get better, even the width of critical land and erotion got more increase. It was causedof some factors, those are unaccurateness of program and technological aplication. Analysis of thisresearch was focused on unaccurateness of strategic program. It wos to analysis and to formulate (1)main strategic program, and (2) suppoort strategic program on planning, actuating, and controlling ofcritical land bila watershed management. Analysis of Interpretative Structural Modelling was applied onthis research, and the result shown that main strategic program must be applicated with : (1) to equalizevision and mission on watershed management was carried out according to cross territory, (2) toorganize planning pattern on integrated watershed, (3) to coorporate in fund of cross territory, and (4) todevelop monitoring and evaluating function of cross territory. Were as support strategic program were(1) to form watershed management coordination organization, (2) to develop contolling function and lowinvestment cross territory.